Provision of a public good with altruistic overlapping generations and many tribes - Larry S. Karp (Center for Economic Studies and ifo Institute (CESifo), 2012)
Intergenerational altruism and contemporaneous cooperation are both important to the provision of long-lived public goods. Equilibrium climate protection may depend more sensitively on either of these considerations, depending on the type of policy rule one examines. This conclusion is based on a model with n tribes, each with a sequence of overlapping generations. Tribal members discount their and their descendants' utility at different rates. Agents in the resulting game are indexed by tribal affiliation and the time at which they act. The Markov Perfect equilibrium is found by solving a control problem with a constant discount rate and an endogenous annuity.
Keywords: C73; D62; D63; D64; H41; Q54; 330; overlapping generations; altruism; time consistency; Markov Perfection; differential games; climate policy; Öffentliches Gut; Altruismus; Overlapping Generations; Klimaschutz; Generationenbeziehungen; Dynamisches Spiel; Theorie